Analisis sifat dasar kayu hasil hutan tanaman rakyat - I Kentut Pandit; Dodi Nandika; I Wayan Darmawan (Jurnal Ilmu Pertanian Indonesia, 2011)
The research done based on the fact that the log from natural forest could not fullfil the need of domestic forest industry. Annual available cut from natural forest in the year 2007 was only 9.1 million m3 while forest industry domestic country in the year 2005 reached 44.5 million m3.  Raw material crisis was the most problem facing by domestic forest industry and the solution could be come soon as posible. The establishment of social plantation forest is one of the government program to solved the lack of forest industry raw materials. The species for social plantation forest are available more than enough. Previous research done in the year 2009 shown taht most of HTR log was small diameter, short sortimen, heart wood presentation of juvenile wood was very high. The result of research shown that the basic characteristics of three species of HTR namely: Jabon, sengon and pulai have a good colour (bright), moderate texture, fibre is slim to interlocked, have no decoratif form, bulk density low. The characteristic of 6 species HTR was: variation in colour, good texture until moderate, fibre direct until interlocked, the wood have beautiful decoration, moderate bulk density. Basic of characteristic of wood is very important in affacting the quality of the products. An effort to increase the quality of HTR wood should be done so that the use of HTR product becaming important to suggest the developing of creative industry.